2017
DOI: 10.1093/jpids/pix070
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionate Exposure to Antibiotics in Children at Risk for Invasive Pneumococcal Disease: Potential for Emerging Resistance and Opportunity for Antibiotic Stewardship

Abstract: We compared antibiotic prescribing for children with and those without an underlying chronic condition associated with increased risk for invasive pneumococcal disease. Children with a chronic condition had significantly greater cumulative exposure to antibiotics and higher rates of prescriptions per person-year than those without a chronic condition; this population is at increased risk for the emergence of multidrug-resistant pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…The strains of nonsurvivors in this study were multi-drug resistant. Domestic and foreign reports also showed that S. pneumoniae was generally multi-drug resistant, and the resistance to penicillin and cephalosporins increased [ 6 , 26 , 27 ]. Compared with drug sensitivity analysis in the present study, a better consistency rate was achieved if the choice of antibiotics strictly abided by China’s “Guidelines for the Management of Community Communicable Pneumonia (2013 Revision)”.…”
Section: Discussionmentioning
confidence: 99%
“…The strains of nonsurvivors in this study were multi-drug resistant. Domestic and foreign reports also showed that S. pneumoniae was generally multi-drug resistant, and the resistance to penicillin and cephalosporins increased [ 6 , 26 , 27 ]. Compared with drug sensitivity analysis in the present study, a better consistency rate was achieved if the choice of antibiotics strictly abided by China’s “Guidelines for the Management of Community Communicable Pneumonia (2013 Revision)”.…”
Section: Discussionmentioning
confidence: 99%
“…Children demographic and clinical characteristics that could be of interest were extracted from the MHDR including (a) demographics: sex, race/ethnicity, class‐of‐age at the visit; (b) clinical diagnosis: identified in the discharge summary of the visit, by the primary diagnosis code based on International Classification of Diseases, ninth revision (ICD‐9) and tenth revision after 2015 (ICD‐10), including otitis, tonsillitis/pharyngitis, sinusitis, pneumonia, upper respiratory tract infections (URTIs), flu, rhinopharyngitis, bronchitis, laryngitis/tracheitis, infectious gastroenteritis and urinary tract infections; (c) comorbid conditions: children with at least one record documenting a specific condition were categorised as having that condition from the earliest coding occurrence in the visit or in the previous 12 months (evaluation of the comorbid conditions of the 2007 admissions included the screening of the previous year: 2006). The comorbidities were defined using the validated ICD algorithms of Feudtner et al 15 added to the conditions recognised by the Committee on Infectious Diseases of the American Academy of Pediatrics (AAP, 2012 Report) 1,16 ; and (d) site of visits (PC or ER) from the admission records.…”
Section: Methodsmentioning
confidence: 99%
“…Antimicrobials are among the most widely prescribed therapeutic agents 1,2 . Inappropriate use of antibiotics is a public health problem and contributes to the emergence of antibiotic resistance 1,2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations